Sul liberalismo politico e la giustizia come equità - Veca, Salvatore (Philosophy Kitchen - Rivista di filosofia contemporanea, 2018)
The author focuses on the fundamental lines of his interpretation of political liberalism and its relation to the idea of justice as fairness. In Sections 1-7, the liberal theory of the just society is delineated in relation to the historical, academic and political context in which the ideas of political liberalism were formulated. In Sections 8-10, the author introduces the question of global justice, considered as the main conundrum of contemporary political philosophy.